1985
DOI: 10.1136/pgmj.61.719.811
|View full text |Cite
|
Sign up to set email alerts
|

A case of ocular toxicity to ethambutol—an idiosyncratic reaction?

Abstract: Summary:Optic neuritis, a well known adverse effect of ethambutol, is related to the dose and duration of the therapy. The patient described here developed rapidly progressive deterioration of vision after only 3 days oftreatment with ethambutol. Such a case has not been reported before and it is suspected that this was an idiosyncratic reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 6 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Although it is not a typical bitemporal haemianopia, which should respect the central vertical meridian, many authors have described it for EON (ref. [19][20][21][22][23] ). Heng et al demonstrated retinal ganglion cell damage in a rat model 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not a typical bitemporal haemianopia, which should respect the central vertical meridian, many authors have described it for EON (ref. [19][20][21][22][23] ). Heng et al demonstrated retinal ganglion cell damage in a rat model 24 .…”
Section: Discussionmentioning
confidence: 99%
“…This inhibition may extend to mammalian cells and especially the mitochondrial DNA. Apart from anecdotal idiosyncratic reactions, this toxicity is largely dose and duration dependent [2].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Poussos and Tsolkas found a 2% incidence of ocular toxicity among 250 patients receiving 15 mg/kg EMB daily for 4 -8 months. [7,13,14] Although often reversible when the drug is discontinued early, many reports exist of permanent blindness following EMB treatment at the standard dosage. Because the risk of ocular toxicity is increased in patients with renal failure, the maximum recommended dose is 15 mg/kg/day, and the dosage of EMB should be adjusted according to residual renal function.…”
Section: Discussionmentioning
confidence: 99%
“…[7] The maximum recommended dose (conventional dosage) for healthy people is 25 mg/kg/day, and this dose is generally only given for first two months of the therapy, after which it is reduced to 15 mg/kg/day. [1,7,13] Owing to the similarities between the toxic optic neuropathy of EMB and nutritional (tobacco/alcohol) amblyopia, parenteral hydroxocobalamin therapy (vitamin B12) has been studied as a possible treatment for restoring vision loss. Meanwhile, the recommended dose for ESRD patients is 15 mg/kg QOD.…”
Section: Discussionmentioning
confidence: 99%